An extensive intraoral blue nevus in an elder patient - Cunha, John Lennon Silva; Tomo, Saygo [UNESP]; Marinho Neto, Edmundo; Silva, João Vitor Rocha; Melka Coelho, S.; de Carvalho Melo, Allan Ulisses; de Albuquerque-Júnior, Ricardo Luiz Cavalcanti (Wiley, 2021)
Objective: To report a rare case of intraoral extensive blue nevus in an elder patient. Background: Oral blue nevi is a well-recognised skin melanocytic neoplasm that rarely occurs in the oral cavity and may mimic melanoma in the early stages. Methods: An incisional biopsy was performed, and the diagnosis was blue nevus. Conclusion: Both the clinician and pathologist must be aware of such a presentation to diagnose and treat appropriately.
Keywords: Blue nevus; Melanin; palate